Analisis Teori Belajar Kontruktivisme - Tiara Nurhayati; Zullysa, Deka; Muhammad Dhori; Nurzarah Adelia (STAI AL-AMIN, 2025)
Learning theories still evolve with the dynamics of life, starting from the theory of behaviorism to other theories such as constructivism. Every new theory emerges to look at, criticize, and correct the shortcomings of previous theories.The above research employs the method of literature review, which directs to a number of journals on stimulus-response, in order to search for relevant theories to use as references. Is written using the descriptive analysis method, which is interpreting the meaning of references to the topic and title of research. The researcher collected, read, and summarized available references, later explained them in their own words.